Potential effects of lipid lowering and antioxidant activity of exosomes from Phascolosoma esculenta: in vivo and in vitro studies - Yang, Lin; Yi, Xue; Duan, Meitao; Mahal, Ahmed; Chen, Binbin; Zhang, Zhiqiang; Ren, Jungang; Chen, Ming; Meng, Chen; Xu, Moxun; Obaidullah, Ahmad J.; Wang, Chen; et al. (Frontiers in Pharmacology, 2025)
Exosomes released from cells have been shown to play an important role in health and disease due to their potential application in therapy and diagnosis. First of all, we extracted the exosome from Phascolosoma esculenta, and studied the lipid lowering and antioxidant activity of Phascolosoma esculenta exosome. It was found that Phascolosoma esculenta exosomes could significantly decrease the lipid accumulation caused by oleic acid, and improve triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and low density lipoprotein (LDL-C). The exosomes of Phascolosoma esculenta also exhibit antioxidant activity, which can decrease the amount of reactive oxygen species (ROS) and malondialdehyde (MDA), and raise the level of superoxide dismutase (SOD) and total antioxidant capacity (T-AOC). The exosomes of Phascolosoma esculenta have the function of reducing lipid and antioxidation.